2014
DOI: 10.1080/02642069.2014.942652
|View full text |Cite
|
Sign up to set email alerts
|

Recovering service failure through resource integration

Abstract: Customers and employees can co-create a resolution following a service failure through integrating their resources. Their activities and interactions during resource-integration shape the customers' service recovery experiences. Prior research overlooks resource integration between all involved actors in a co-created service recovery process. This research details the process with two empirical studies. Study 1 is a qualitative analysis of narratives of service recovery experiences; Study 2 is a quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 41 publications
(66 reference statements)
0
43
0
Order By: Relevance
“…Second, as Xu et al (2014b) have noted, resource integration in service recovery is always context-specific and experiential. Thus, understanding the context-specific factors that affect co-recovery behaviour could provide fruitful insights.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, as Xu et al (2014b) have noted, resource integration in service recovery is always context-specific and experiential. Thus, understanding the context-specific factors that affect co-recovery behaviour could provide fruitful insights.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…We treat it as a multi-dimensional construct (second order factor) by showing that consumers co-recover through information sharing, responsible behaviour, and personal interaction. Our treatment of co-recovery in-role behaviour as a cocreation in-role behaviour after a service failure (by sharing the same dimensions) is based on the work of Xu et al (2014b) who argued that customers are also resource integrators in a service recovery context as they are involved in service delivery.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong, Evans, and Zou [30] first introduced customer participation in service recovery and defined it as "the degree to which the customer is involved in taking actions to respond to a service failure". Scholars have verified that customer participation can lead to positive post-recovery behavior, such as perceived service quality [32], satisfaction and repurchase intention [25,34], positive word of mouth [16,38], experience with service recovery [39], and intention for future co-creation [31,40].…”
Section: Customer Participation In Service Recoverymentioning
confidence: 99%
“…Because customer participation can bring the above advantages, scholars have found that customer participation can enhance the effect on customers' cognition, including perceived justice [2,25,28,39,41], perceived match [31], perceived value [41], perceived control [42], and perceived co-creation [38]. Furthermore, positive and negative emotions [43] and affect [44] have been used to explain the role of customer participation in customers' emotions.…”
Section: Customer Participation In Service Recoverymentioning
confidence: 99%